Institutional Pressures and Procurement Cycle Time in Uganda’s Central Government Procuring and Disposing Entities: The Mediating Role of Opportunistic Behavior Ab - Olupot,Simon Peter (Emerald Publishing Limited, 2023)
This study focused on establishing the mediating role of opportunistic behavior in the relationship between institutional pressures and procurement cycle time (PCT) in Uganda’s central government (CG) procuring and disposing entities (PDEs). The study also sought to establish the relationship between institutional pressures and PCT, between institutional pressures and opportunity behavior and between opportunistic behavior and PCT. This study was carried out because most PDEs had failed to perform well in terms of PCT, and beneficiaries had often complained of the lengthy PCT.